Assessment of environmental flows for the Upper Ganga Basin. - O'Keeffe, J.; Kaushal, N.; Bharati, Luna; Smakhtin, Vladimir U. (World Wide Fund for Nature, 2012)
Ecosystem integrity as well as the goods and services offered by the rivers in India are getting adversely affected by changes in quantity quality and flow regimes. Growing water abstractions for agriculture domestic industrial and energy use are leaving many rivers running dry while others are becoming severely polluted. The mighty Ganga is no exception. During its 2,525 km journey from Gangotri to Ganga Sagar there are complex, nested sets of challenges that threaten the very existence of the holy river revered by millions of Indians. In the upper Himalayan reaches the flow in the river is vulnerable to water abstractions by hydropower projects both existing and proposed. From the time the river enters the plains abstractions for agriculture urban and industrial uses leave the river lean and polluted. As the river's dynamics have been altered by diversions and inefficient use the freshwater flow has reduced leading to a reduction in the rivers assimilative capacity. As the river makes its way to the sea and more pollution is added to the lean flows the stress on the Ganga increases. Climate change is adding another set of complexities to the problems of the Ganga and to the hundreds of millions of people who depend on the river and its basin.